Real-World Comparative Evaluation of Add-On Glucagon-like Peptide 1 Receptor Agonist in Type 2 Diabetes Treated with or without Insulin - Hsuan-Wen Chou; Kai-Pi Cheng; An-Chi Lin; Hao-Chang Hung; Ching-Han Lin; Chih-Chen Wang; Hung-Tsung Wu; Horng-Yih Ou (MDPI AG, 2022)
Glucagon-like peptide 1 receptor agonist (GLP-1 RA) is a potent antidiabetic agent with cardiorenal and weight-losing benefits in patients with type 2 diabetes (T2D). The combination of GLP-1 RA with basal insulin has been suggested in several clinical studies as a useful treatment for intensifying insulin therapy in T2D. However, there has been no real-world evidence study comparing the glycemic effects of GLP-1 RAs add-on to background treatment with and without insulin. A retrospective study was performed in 358 patients with T2D who initiated liraglutide or dulaglutide. Among them, 147 patients were prior and concurrent insulin users, and 211 patients were non-insulin users. After 12 months of GLP-1 RA treatment, the changes in hemoglobin A1c (HbA1C) and body weight were evaluated. The effectiveness of GLP-1 RAs on HbA1C reduction was greater in insulin users than non-insulin users at 12 months (−1.17% vs. −0.76%; p = 0.018). There was no significant difference in body weight change between insulin users and non-insulin users at 12 months (−1.42 kg vs. −1.87 kg; p = 0.287). The proportion of responders (decrease of HbA1C > 1%) in insulin users was much higher than that in non-insulin users (48% vs. 37 %; p = 0.04). In insulin users, those who had increased insulin dosage at 12 months had significantly less HbA1C reduction than that of non-increased patients (−0.62% vs. −1.57%; p = 0.001). GLP-1 RAs provide superior glucose-lowering effects in insulin-treated patients compared with non-insulin-treated patients with T2D without significant differences in body weight decrease.